PROFIL POLA ASUH ORANG TUA PESERTA PROGRAM PARENTING (Studi Pada Orang Tua Peserta Program Parenting Di Kelurahan Gegerkalong Kecamatan Sukasari Kota Bandung) - Do`a Fajarwati, - (2020)
Socio-cultural development can not be separated from the teaching that is applied in the family, the problem of parenting is currently a concern of all parties because in reality it can be seen still in the environment around parents who treat their children harshly such as scolding to shouting in front of many people, shouting, hit and pinch on the grounds of giving lessons to children. Awareness of the importance of parenting by parents made many parties moved to hold a Parenting Program, one of which is in Gegerkalong Village with parent participants who have early childhood. The purpose of conducting the research are: 1) describing and analyzing the involvement of parents in the Parenting Program, 2) describing and analyzing how parenting is done by parents who follow the Parenting Program. This study uses a qualitative approach with a descriptive method of qualitative research methods also called naturalistic research methods because the research is carried out in very natural conditions (natural setting). Data collection through participatory observation, structured and unstructured interviews. documentation study using tools: observation guide, interview guide, field notes, data validation using triangulation (technique, data, time) as well as analysis using reduction, data presentation and drawing conclusions. The focus of this research is on the three institutions that have routinely held Parenting Programs namely PAUD Miana V, PAUD Bani Soleh and PAUD Pelita Bunda limiting research on parents who participate in the Parenting Program at the Institute with a variety of jobs, latest education, age and neighborhood where people live old. There are two groups of parents involved in the parenting program, namely active and passive groups. Active groups are groups that are involved in helping all preparations from before they are carried out to completion. This group is characterized by; 1) have a high motivation to join the program because they have knowledge needs about caring for care in the family; and 2) have a relationship and involvement in various activities carried out by PAUD institutions so far.